Gending Sekatian di Desa Adat Tejakula - I Ketut Aditya Putra; Hendra Santosa (Journal of Music Science, Technology, and Industry, 2021)
Purpose: The purpose of this study was to determine and describe the form of performances from Gending Sekatian in the Tejakula Traditional Village, Buleleng Regency. Research methods: The research method applied is descriptive qualitative using data collection techniques, namely observation, interviews, documentation and literature. The theory used to examine in this research is the form theory proposed by Clive Bell. Results and discussion: The results of this research on the form of Gending Sekatian show, which can be seen from some of the forming elements in it. As with the types of instruments used, they are divided into five different functions. Each of these instruments is adjusted according to their respective functions, consisting of penandan gending instruments, types of bantang gending instrument, types of pepayasan instruments, types of pesu-mulih instruments, and types of pepayasan instruments. Implication: Based on all the elements mentioned above, basically it becomes important when Gending Sekatian is presented to accompany the religious ritual procession (dewa yadnya) carried out by the community at Pura Maksan, Tejakula Traditional Village, Buleleng Regency.